Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

x⁴+5x²-6=0 solve for x

Sagot :

Let u = x², then we would have u² + 5u - 6 = 0

From here, we can factor it and get us (u-1)(u+6) = 0

So our solution for u is u = -6 or 1.

Now substitute u back to x².

x² = -6 or 1

x = ±√(-6) or ±√1

Since ±√(-6) is not real number, we ignore it.

Which leave us x = ±√1 = ±1

So our real solution is x = -1 or 1.